Sorafenib Modulates the LPS- and Aβ-Induced Neuroinflammatory Response in Cells, Wild-Type Mice, and 5xFAD Mice - Kim, Jieun; Park, Jin-Hee; Park, Seon Kyeong; Hoe, Hyang-Sook (Frontiers in Immunology, 2021)
Sorafenib is FDA-approved for the treatment of primary kidney or liver cancer, but its ability to inhibit many types of kinases suggests it may have potential for treating other diseases. Here, the effects of sorafenib on neuroinflammatory responses in vitro and in vivo and the underlying mechanisms were assessed. Sorafenib reduced the induction of mRNA levels of the proinflammatory cytokines COX-2 and IL-1β by LPS in BV2 microglial cells, but in primary astrocytes, only COX-2 mRNA levels were altered by sorafenib. Interestingly, sorafenib altered the LPS-mediated neuroinflammatory response in BV2 microglial cells by modulating AKT/P38-linked STAT3/NF-kB signaling pathways. In LPS-stimulated wild-type mice, sorafenib administration suppressed microglial/astroglial kinetics and morphological changes and COX-2 mRNA levels by decreasing AKT phosphorylation in the brain. In 5xFAD mice (an Alzheimer’s disease model), sorafenib treatment daily for 3 days significantly reduced astrogliosis but not microgliosis. Thus, sorafenib may have therapeutic potential for suppressing neuroinflammatory responses in the brain.